Students Error in Pronouncing English Post Alveolar Consonants at The Eleventh Grade of Senior High School 1 Jambi City - Viona Aulia Sukma; Yanti Ismiyati; Ridho Praja Dinata (Universitas Batanghari Jambi, 2023)
This research was aimed to find out the student error in pronouncing English post alveolar consonants sound at the eleventh grade of Senior High School 1 Jambi City. The research methodology of this study was qualitative descriptive research which involved the subject. The subject of this research is XI MIPA 2 of Senior High School 1 Jambi City which contains of 36 students. In collecting the data, the researcher gave test and collected the student transcript. The result of the research showed that the eleventh grade students of Senior High School 1 Jambi City got a high percentage of error in pronouncing English post alveolar consonant sounds. The type of error that have very high significance to pronounce by the students is /Ó¡/ sound which is 86%. In contrast with /âˆ«/ sound where the students just made low percentage of an error pronunciation in 14%. From four categories of errors which is addition. Omission, substitution and ordering, the most dominant error made by the students are substitution with percentage 97,7%.